Dataset of the complete mitogenome of the deep-sea sailfin roughshark, Oxynotus paradoxus Frade, 1929 - Matos, Ana (2024)
Chondrichthyans comprise a diverse group of vertebrate species with extraordinary ecological relevance. Yet, multiple members of this evolutionary lineage are associated with sig-nificant extinction risk. The sailfin roughshark Oxynotus para-doxus is a deep-water benthic shark currently listed as vul-nerable due to population declines in parts of its range. Here we provide the first complete mitochondrial genome of O. paradoxus, comprising also the first record for the genus and family Oxynotidae. These data can facilitate future monitor-ing of the genetic diversity in this and related species. Ge-nomic DNA was extracted from O. paradoxus collected in the eastern North Atlantic off western Portugal (37.59 degrees N, 9.51 degrees W) and sent for Illumina Paired-End (2 x 150 bp) library con-struction and whole genome sequencing on a Novaseq60 0 0 platform. Trimmomatic (version 0.38) was used to remove adapters and MitoZ (version 3.4) to assemble and anno-tate the mitogenome. This mitogenome with 17 100 bp has a total of 38 genes, 13 of which are protein-coding genes, 23 transfer RNA genes, and 2 ribosomal RNA genes. Eight transfer RNAs and 1 protein-coding gene (NADH de-hydrogenase subunit 6, NAD6) are in the complementary strand. In the provided phylogenetic inference, with all avail-able and verified Squalomorphii mitogenomes, the four or-ders are well separated, and as expected, O. paradoxus is placed in the Squaliformes order. This data reinforces the need for more genomic resources for the Oxynotidae family.(c) 2023 The Author(s). Published by Elsevier Inc. This is an open access article under the CC BY-NC-ND license ( http://creativecommons.org/licenses/by-nc-nd/4.0/ )